On the Lateral Entrainment Instability in the Inner Core Region of Tropical Cyclones - Zhu, Ping; Zhang, Jun A.; Marks, Frank D. (Geophysical research letters, 2023)
Entrainment of dry moat air with low equivalent potential temperature laterally into the eyewall and rainbands is a unique turbulent process in the inner‐core region of a tropical cyclone (TC). By analyzing in‐situ aircraft measurements collected by the reconnaissance flights that penetrated the eyewalls and rainbands of Hurricanes Rita (2005), Patricia (2015), Harvey (2017), and Michael (2018), as well as numerical simulations of Hurricanes Patricia (2015), and Michael (2018), we show that the moat air entrained into the eyewall and rainbands meets the instability criterion, and therefore, sinks unstably as a convective downdraft. The resultant positive buoyancy fluxes are an important source for the turbulent kinetic energy (TKE) in the eyewall and rainband clouds. This mechanism of TKE generation via lateral entrainment instability should be included in the TKE‐type turbulent mixing schemes for a better representation of turbulent transport processes in numerical forecasts of TCs. Plain Language Summary Turbulence is commonly regarded as a chaotic flow feature pertaining to the planetary boundary layer (PBL). In the inner core of a tropical cyclone (TC), however, turbulence can also be generated in the eyewall and rainbands above the PBL by cloud processes. The turbulence at the edge of the eyewall/rainbands not only experiences the large lateral thermodynamic contrasts across the interface between clouds and moat but also entrains moat air into clouds. Previous studies suggest that under certain conditions the entrained air into the clouds can sink unstably as convective downdrafts, leading to the generation of turbulent kinetic energy (TKE) in the clouds. By analyzing in‐situ aircraft measurements collected during the reconnaissance flights that penetrated the eyewalls and rainbands of Hurricanes Rita (2005), Patricia (2015), Harvey (2017), and Michael (2018), as well as numerical simulations of Patricia (2015) and Michael (2018), this study shows that the moat air entrained into the eyewall and rainbands meets the instability criterion. An estimate of the entrainment buoyancy fluxes suggests that the lateral entrainment instability is an important source of TKE in the eyewall and rainbands, and thus, it needs to be included in the TKE‐type turbulence schemes used in numerical forecasts of TCs. Key Points Lateral entrainment of air from the moat region into eyewall and rainbands of a tropical cyclone (TC) satisfies the instability criterion Positive buoyancy flux induced by the entrainment is an important source of turbulent kinetic energy for the eyewall and rainband clouds Lateral entrainment instability should be included in turbulent mixing parameterizations in TC forecast models